Determinants of healthcare workers perceptions, acceptance and choice of COVID-19 vaccines: a cross-sectional study from the United Arab Emirates. Issue 1 (31st December 2022) - Saddik, Basema; Al-Bluwi, Najlaa; Shukla, Ankita; Barqawi, Hiba; Alsayed, Hawra Ali Hussain; Sharif-Askari, Narjes Saheb; Temsah, Mohamad-Hani; Bendardaf, Riyad; Hamid, Qutayba; Halwani, Rabih
ABSTRACT: Acceptance of COVID-19 vaccine among health-care workers (HCWs) is crucial for controlling the pandemic and ensuring HCW and patient safety. Information on the acceptance of different COVID-19 vaccines is lacking. Despite the United Arab Emirates (UAE) having vaccinated most of its population, vaccine acceptance still raises concerns. This study explores COVID-19 vaccine acceptance, vaccine choice, and associated factors among HCWs in the UAE. An online national cross-sectional study was conducted among 517 HCWs. Acceptance and choice of COVID-19 vaccines were assessed, and logistic regression analysis identified predictors for vaccine acceptance. More than half (58%) of HCWs were willing to take the vaccine and give it to their family. Reasons for taking the vaccine were concerns for families contracting COVID-19 (67%) and social responsibility (64%). Reasons for refusals included concerns with side-effects (61%). Most HCWs knew of the Pfizer (79%) and Sinopharm (57%) vaccines; however, acceptance was higher for Pfizer (35%) and AstraZeneca (21%) vaccines. Being male and being influenza vaccinated predicted willingness to take the vaccine (aOR: 2.34; 95% CI:1.34–4.08; p ≤ 0.001) and (aOR: 2.13; 95% CI: 1.29–3.51; p ≤ 0.001), respectively. HCWs who expressed concerns with inadequate safety data were less likely to take the vaccine (aOR: 0.17; 95% CI: 0.10–0.30; p ≤ 0.001). Additionally, side effects, perception of risk, and level of trust of company and country of manufacture predicted acceptance and choice of vaccines. Effective vaccine policy campaigns to improve acceptance should target HCW's knowledge and awareness of perceived risks of COVID-19, safety data, social responsibility, and individual preferences for vaccine choice.